Webdoc Mirages: Innovation and Participation for the Representation of Refugees - Lara Martínez, María; Bueno Doral, Tamara; Palazón Meseguer, Alfonso (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In this article we present the process of creating the webdoc Mirages, framed in the European research project on refugees RAISD. The webdoc is based on a participatory research process through the involvement of all the main stakeholders. The webdoc is created, as a way of spreading the main research results, with the aim of improving the dissemination about the situation of that vulnerable group. This communication also investigates the lines of confluence that exist between the traditional documentary and interactive multimedia approaches, which offer new models of creation and consumption.